2002
DOI: 10.1063/1.1498962
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state decomposition of silicon carbide for growing ultra-thin heteroepitaxial graphite films

Abstract: Using grazing-incidence x-ray diffraction and scanning tunneling microscopy (STM), we show that the thermal decomposition of an electronic-grade wafer of 6H-SiC after annealing at increasing temperatures TA between 1080 and 1320 °C leads to the layer-by-layer growth of unconstrained, heteroepitaxial single-crystalline graphite. The limited width of the in-plane diffraction rod profiles of graphite reveals large terraces, with an average size larger than 200 Å and a very small azimuthal disorientation. The over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
166
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(187 citation statements)
references
References 43 publications
14
166
0
4
Order By: Relevance
“…6 These unique features, coupled with the fact that multilayer graphene can be grown and patterned on SiC, provide an important foundation for graphene based electronics. 7 The discovery that an applied electric field induces a band gap in bilayer graphene 6 has generated great interest in the effects of external fields on graphene structures. McCann 8 developed a tight-binding model for bilayer graphene and found a linear relationship between the induced band gaps and induced charges in the bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…6 These unique features, coupled with the fact that multilayer graphene can be grown and patterned on SiC, provide an important foundation for graphene based electronics. 7 The discovery that an applied electric field induces a band gap in bilayer graphene 6 has generated great interest in the effects of external fields on graphene structures. McCann 8 developed a tight-binding model for bilayer graphene and found a linear relationship between the induced band gaps and induced charges in the bilayer.…”
Section: Introductionmentioning
confidence: 99%
“…On 4H-Si and 3C-Si, the carbon buffer layer atoms are strongly bonded to the substrate and form a ð6 ffiffi ffi 3 p  6 ffiffi ffi 3 p ÞR30 surface reconstruction, [25][26][27] while on 4H-C, there is no unique surface reconstruction. 28 In our optical model, the interface layer accounts for this buffer layer, and also the roughness of the substrate surface, an effect of the slight off-axis cut of the SiC substrate, and non-uniform sublimation of silicon from the SiC substrate.…”
mentioning
confidence: 99%
“…[7,8,9] These studies showed that graphite grows epitaxially on the (0001) Siterminated (Si-face) surface of SiC, while graphite grown on the C-terminated (0001) (C-face) surface was rotationally disordered and under some conditions formed nanocaps instead of a smooth film. [10] Consequently, the C-face was initially overlooked as a potential substrate for graphene-based electronics.…”
mentioning
confidence: 99%
“…The graphite film thickness for all samples was determined by measuring the x-ray intensity as function of ℓ along the graphite (1,1, ℓ) G rod. [8] The notation (h, k, ℓ) G identifies a reciprocal-space point in units of the graphite hexagonal reciprocal lattice basis vectors: a * G = 2.9508 Å −1 and c * G = 1.8829 Å −1 . Unsubscripted reciprocal-space coordinates (h, k, ℓ) refer to the substrate 4H-SiC hexagonal recip- A reciprocal space schematic for epitaxial graphene on SiC is shown in Fig.…”
mentioning
confidence: 99%